An Energy Efficient Routing Algorithm For Wban - et. al., Kushnian Kour, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The wireless body area network is the decentralized and dynamic type of network in which sensor nodes can be added dynamically. The RPL is the routing protocol which is used to establish path from source to destination. The SEAR protocol is the improved version of RPL routing protocol. In this research paper, problem of link failure is resolved with the parameters of buffer size. The proposed mode is implemented in MATLAB and compared with basic SEAR protocol in terms of certain parameters. It is analyzed that proposed model performs well in terms of energy consumption, packet loss and throughput.